2011
DOI: 10.2337/db10-0789
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Insulin Secretion and Enhanced Insulin Sensitivity in Cholecystokinin-Deficient Mice

Abstract: OBJECTIVECholecystokinin (CCK) is released in response to lipid intake and stimulates insulin secretion. We hypothesized that CCK deficiency would alter the regulation of insulin secretion and glucose homeostasis.RESEARCH DESIGN AND METHODSWe used quantitative magnetic resonance imaging to determine body composition and studied plasma glucose and insulin secretion of CCK gene knockout (CCK-KO) mice and their wild-type controls using intraperitoneal glucose and arginine infusions. The area of anti-insulin stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 38 publications
5
39
1
Order By: Relevance
“…In addition, we observed consistent improvement of insulin sensitivity with both the hybrid peptide and (pGlu-Gln)-CCK-8 in combination with exendin-4 by the end of the treatment period. This is in agreement with the well-known insulin-sparing actions of GLP-1 (34), and evidence also suggests an integral role for CCK as a regulator of insulin action, especially under conditions of high-fat feeding (35). In this study the islet number, together with both islet area and b-cell area, were increased by all treatment modalities.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, we observed consistent improvement of insulin sensitivity with both the hybrid peptide and (pGlu-Gln)-CCK-8 in combination with exendin-4 by the end of the treatment period. This is in agreement with the well-known insulin-sparing actions of GLP-1 (34), and evidence also suggests an integral role for CCK as a regulator of insulin action, especially under conditions of high-fat feeding (35). In this study the islet number, together with both islet area and b-cell area, were increased by all treatment modalities.…”
Section: Discussionsupporting
confidence: 78%
“…(pGluGln)-CCK-8 also stimulated insulin secretion from clonal beta cells and acutely improved glucose homeostasis in ob/ob and high-fat-fed mice. These observations demonstrate the glucose-lowering potential of CCK consistent with a beta cell effect under specific conditions such as high-fat feeding [22]. Upregulation of CCK actions is also evident in mice with double genetic knockout of GLP-1 and GIP and in pregnancy, where enhanced beta cell action are key features [23,24].…”
Section: Discussionsupporting
confidence: 60%
“…This has been observed in previous work in animals maintained on a high fat diet (27). The impact of glucose on CCK expression may be as a result of the interaction of CCK with insulin.…”
Section: Cholecystokininsupporting
confidence: 64%
“…Lo (2011) using CCK-KO mice, found that when maintained on a low-fat diet animals had a reduced acute insulin response to glucose (27). However, when maintained on a high fat diet, CCK-KO mice developed glucose intolerance.…”
Section: Cholecystokininmentioning
confidence: 99%